Religious Responses to Agricultural Crises: Exploring the Diverse Patterns in Garut, Indonesia - Shodiqin, Asep (UIN Sunan Gunung Djati Bandung, 2024)
This study explores the critical role of religious patterns in shaping responses to agricultural crises, specifically focusing on the failure of the strawberry harvest in Barudua Village, Garut, West Java. The research employs a qualitative case study approach, examining three distinct sub-villages, each with unique religious practices: exclusive-protective, participatory, and progressive. Through interviews, observations, and thematic analysis, the study reveals how these religious patterns influence the community's resilience and adaptability in the face of crisis. The findings indicate that while exclusive-protective patterns tend to foster passivity, participatory and progressive patterns encourage community engagement, innovation, and social cohesion. These results suggest that integrating religious perspectives into agricultural crisis management can enhance community resilience and offer sustainable solutions. This research provides practical insights for policymakers and community leaders, empowering them to develop culturally sensitive and effective strategies for managing agricultural challenges.